ANALISIS PERBEDAAN RETURN SAHAM JAKARTA ISLAMIC INDEX (JII) DAN INDEKS LQ45 - Purwati Purwati; Tri Rinawati; Aprih Santoso (BBM (Buletin Bisnis & Manajemen), 2020)
The purpose of this study was to determine the effect of Debt To Equity Ratio (DER), Price To Book Value (PBV), Earning Per Share (EPS) on the Jakarta Islamic Index Stock Return and LQ45 Stock Return Index, and to determine the difference in the Jakarta Islamic Index Stock Return with LQ45 Index.The population of this research is the company for the Jakarta Islamic Index shares which are 30 listed companies and the LQ45 Index which is 45 listed companies. The sampling technique uses the Purposive Sampling method.The analysis technique used is the classical assumption test, the Multiple Linear Regression Test, and the Independent Sample t test.Significant value (Sig.) For DER, PBV and EPS for the JII Stock Index greater than 0.05 concluded that the hypothesis was rejected meaning that DER, PBV and EPS had no significant effect on Stock Return. Significant value (Sig.) For DER, PBV and EPS for the LQ45 Stock Index greater than 0.05 for the LQ45 stock index concluded that the hypothesis was rejected meaning that DER, PBV and EPS had no significant effect on Stock Return. There was a significant difference between Stock Returns JII with LQ45 Stock Return means the results obtained from stock investments for each company both JII and LQ45 Index.